Estimation Of The Quality Of Life Benefits Associated With Treatment For Spinal Muscular Atrophy - Lloyd AJ; Thompson R; Gallop K; Teynor M (Dove Medical Press, 2019)
Andrew J Lloyd,1 Robin Thompson,2 Katy Gallop,1 Megan Teynor3 1Acaster Lloyd Consulting Ltd., London, UK; 2Value and Access, Biogen, Baar, Switzerland; 3Value and Access, Biogen, Cambridge, MA, USACorrespondence: Andrew J LloydAcaster Lloyd Consulting Ltd., 16 Upper Woburn Place, London WC1H0BS, UKTel +44 20 3978 1681Email andrew.lloyd@acasterlloyd.comBackground: Spinal muscular atrophy (SMA) is a rare, genetic, progressive neuromuscular disorder characterized by severe muscle atrophy and weakness and is a leading genetic cause of death in infants and children. Nusinersen was the first treatment targeting the underlying cause of disease approved by the FDA, EMA and other countries for patients with SMA. There are currently very limited data available on the health-related quality of life (HRQoL) burden of SMA suitable for use in a cost-effectiveness analysis.Objective: This study was designed to estimate quality of life weights or utilities for different SMA states.Methods: SMA case studies were developed describing Type I (infantile onset) and Type II (later-onset) patients and different outcomes from treatment. These were developed so that quality of life weights or utilities (where the value of health ranges from 1 – full health to 0 – dead) could be estimated for cost-effectiveness analysis. Clinical experts (n=5) rated each of the case studies using standardized HRQoL instruments – the EQ-5D-Y and PedsQL-NMM (baseline states only).Results: The SMA Type I utilities ranged from −0.33 (requires ventilation) to 0.71 (Type I patient reclassified as Type III following treatment), with quite substantial differences between some states. Most Type I states had a utility score below zero indicating the severity of the states. The SMA Type II utilities ranged from −0.13 (worsened) to 0.72 (stands/walks unaided). In general, the results showed HRQoL improved in line with better health states.Conclusion: The utility scores obtained in this study highlight the very substantial burden experienced by SMA patients. Despite the limitations in the methods used, this study produced data with face validity and is a useful starting point for understanding the burden of SMA Types I and II in cost-effectiveness analysis.Keywords: spinal muscular atrophy, health-related quality of life, utility, EQ-5D, cost-effectiveness analysis